REVIEW OF APPLICATION OF INTERNAL CONTROL OF CIGARETTE INVENTORY IN PT. ISWANTO MAKASSAR - Masrullah, Masrullah (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
PT. Iswanto Makassar Is a company engaged in general trading and agents, except travel. This study aims to determine the Application of Internal Control of Cigarette Inventory at PT. Iswanto is in accordance with the Accounting Information System. The valuation method applied by PT. Iswanto Makassar, namely the FIFO (First In First Out) method and the LIFO Method (Last In First Out). While the data collection techniques carried out in this study are Observation, Interview and Documentation Study and the method used to analyze the data obtained is to use Qualitative Methods. Based on the results of the study, it can be stated that the internal control of inventory in the company is in accordance with the Accounting Information System.